Selection of the Best Proposal using FAHP: Case of Procurement of IT Master Plan’s Realization - Amadou Diabagate; Abdellah Azmani; Mohamed El Harzli (Institute of Advanced Engineering and Science, 2017)
IT master plan, which allows planning and managing the development of the computer systems, derives its importance in the central role of the computer systems in the functioning of organizations. This article focuses on the use of FAHP method for analysis and evaluation of tenders during the awarding of contracts of IT master plan’s realization. For those purposes, a painstaking work was realized for making an inventory of criteria and sub-criteria involved in the evaluation of tenders and for specifying the degrees of preference for each pair of criteria and sub-criteria. To find a provider for the IT master plan’s realization, organizations are increasingly using tendering as the mode of awarding contracts. This paper is an improvement of a previous published paper in which AHP method was used. The goals of this work are to make available to members of tenders committee a decision support tool for evaluating tenders of IT master plan’s realization and endow the organizations with effective IT master plans in order to increase their information systems’ performance.